Relationships between Clinical Outcomes of Coronary Heart Disease of Covid-19 Vaccinated Patients with Hypertension - Susika, Lia; Ramatillah, Diana Laila; Elnaem, Mohamad (Newinera Publisher, 2025)
The effects of COVID-19 vaccination on conventional cardiovascular risk rankings for heart disease patients after inoculation need further investigation especially within Southeast Asian medical settings. The research explored hypertension effects on clinical results in CHD patients after receiving COVID-19 vaccinations at a Jakarta referral hospital in Indonesia. Research investigators conducted an observational cohort study by gathering retrospective and prospective data from January 2022 until May 2024. The clinical investigation evaluated 110 vaccinated patients who had CHD while examining population characteristics, blood pressure status, and their ultimate outcomes between survival and fatal termination. The research included statistical methods that combined Chi-square and Fisher's exact tests for categorical data analysis along with t-tests for age analysis, one-way ANOVA for subgroup analysis, Pearson correlation and binary logistic regression.. Out of the 110 patients screened for hypertension the condition was observed in 93.6%. Among hypertensive patients survival rates reached 91.3% whereas non-hypertensive patients demonstrated survival rates of 57.1% (p = 0.027). Age proved significant as a predictor of mortality and recovery duration through continuous analysis (p = 0.035; β = 0.42, p = 0.002) even though results were non-significant when patients were grouped as <60 and ≥60 years (p = 1.000). The analysis from logistic regression showed that hypertension worked as a positive predictor for patient survival with an OR of 5.33 (95% CI: 1.02–27.79) and p = 0.047. The vaccine acts as an acute disease protector yet changes but does not completely eliminate existing cardiovascular disease susceptibilities.